The grammar uses of " Lao " in the poetry of Al- Sharif Al- Rada: Collection and Study - Moussa, Khalid Adam (Journal of Humanities & Social Sciences, 2021)
This study aims to bring out some of the grammatical aspects that were included in the book of Al- Sharif Al- Radhi. It aims to study “Lao” (that is mean = if in Arabic language) in practice, by citing some verses that contain “Lao”. Following the descriptive and analytical approach. Where I put a title for the topic of the research, define the topic that was set for the research, and come to the house that was cited, document it, clarify the meanings of difficult words, while documenting this, and expressing the house, extracting the citation, and clarifying the face of citation in it, and citing the Quranic verses. To support and clarify the grammatical rule. And then I reached the most important results, which proved the following: That lao(if) is one of the condition tools that is brought to hold the causation between two sentences, that is, the link between the content of the two sentences, so that the content of the condition is a reason for the content of the answer. That (if) is used for the second abstinence, which is the recompense for the first abstention, which is the condition; This is the well- known saying of the majority of grammarians, and it was made on the tongues of the analysis. Its grammatical judgment; A conditional is probably not apocopate, unlike a few of them. It is most likely that the two sentences after it are verbs, are two verbs in past in pronunciation and meanings together, or only meaning, that the verb is present and its meaning fluctuates to past while the word remains the same. It is not followed by anything but a verb or an action, an implicit verb explained by an explicit verb after the noun. It is originally used for three basic connotations, which are: 1- The conditional is abstinence and is for comment in the past. 2- Conditional non- abstention: it is for future comment, 3- infinitive: It is synonymous: that the infinitive is in the meaning and the casting, but it is not in the subjunctive. It occurs most often in the past and present tense after: to be affectionate. For each one there is example from the poetry of Al- Sharif Al- Radhi. There are other types of (if) that many scholars have presented in grammatical extensions and linguistic; I referred to it in passing, due to the lack of citation it in the book of Al- Sharif Al- Radi. Among these meanings: wishful, provoking, and offering.